1998
DOI: 10.1016/s0022-5347(01)63009-x
|View full text |Cite
|
Sign up to set email alerts
|

Encrusted Cystitis and Pyelitis

Abstract: Early clinical and bacterial diagnosis of encrusted cystitis and pyelitis could improve the prognosis of these infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
118
1
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 42 publications
1
118
1
8
Order By: Relevance
“…Corynebacterium urealyticum is a gram-positive commensal microorganism of the skin [5]. Urinary infections due to this bacterium require three conditions to cause alkaline-encrusted cystitis: a clinical context with immunosuppression or prolonged antibiotic therapy; urologic procedures either surgical or endoscopic, and an inflammatory or neoplastic pre-existing lesion of the urothelium [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corynebacterium urealyticum is a gram-positive commensal microorganism of the skin [5]. Urinary infections due to this bacterium require three conditions to cause alkaline-encrusted cystitis: a clinical context with immunosuppression or prolonged antibiotic therapy; urologic procedures either surgical or endoscopic, and an inflammatory or neoplastic pre-existing lesion of the urothelium [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary infections due to this bacterium require three conditions to cause alkaline-encrusted cystitis: a clinical context with immunosuppression or prolonged antibiotic therapy; urologic procedures either surgical or endoscopic, and an inflammatory or neoplastic pre-existing lesion of the urothelium [5,6]. The delay between the urologic procedure and the diagnosis can vary up to several years [5]. It was demonstrated that its active osteogenic process is reversible, probably by changing the tissue's environmental conditions (reducing inflammation and eradicating infection), suggesting that Corynebacterium urealyticum infection can be considered the 'primum movens' of pathogenic mechanisms behind the bladder tissue calcification [4].…”
Section: Discussionmentioning
confidence: 99%
“…This inflammation, possibly caused by Corynebacterium D2, is commonly associated with instrumentation of the lower urinary tract and can be classified as a nosocomial infection [7] . Corynebacterium D2 is difficult to grow in culture media and requires a prolonged incubation of more than 48 h on special media [1] . In our cases, repeated urine cultures were sterile and perhaps a link to Corynebacterium was not specifically sought [2] .…”
Section: Discussionmentioning
confidence: 99%
“…has sporadically been reported ever since, but has almost been forgotten by urologists and radiologists [1] . It was mainly reported in immunocompromised or debilitated patients after urologic procedures [2] .…”
Section: Imaging Characteristics Of Alkalineencrusted Cystitismentioning
confidence: 99%
“…Los pacientes inmunodeprimidos y en especial los pacientes transplantados 6 , constituyen el colectivo donde más se ha incrementado el diagnóstico de esta patología.…”
unclassified